ANTECEDENT PEER-TO-PEER LENDING INVESTMENT INTENTION IN MANADO - Damian Febrianto Kansil; Joy Elly Tulung; Merinda H. C. Pandowo (FEB Universitas Sam Ratulangi Manado, 2022)
Abstract: The factors that trigger the investment intention of Fintech P2P Lending investors in Manado is still unknown. P2P Lending is at the top of the list of Fintech Development in Indonesia at 2018 with 40% Percentage, which indicated that P2P Lending has a huge opportunity for the investors to find alternative investment instrument. This study aims to determine what factors that significantly influence the intention of P2P Lending investors in Manado to invest in P2P Lending platform. Specifically, in the scope of Perceived Ease of Use, Perceived Usefulness, and Structural Assurance. In this context, Investment Intention is defined as lender behaviour, a will to lend money on P2P Lending platform which also considered as an important step that determined lender interest toward P2P Lending platform. To test the hypotheses that Perceived Ease of Use, Perceived Usefulness, and Structural Assurance has positive significant influence on investment intention, an online questionnaire was distributed to P2P Lending investors in Manado, and the responses were analysed using PLS-SEM analysis with SmartPLS software. The result shows that only Perceived Usefulness has positive significant influence toward Investment Intention. This result concluded that the value of usefulness which bring impact for investorsâ€™ personal is a strong trigger for the investment intention of P2P Lending investors in Manado.Â Abstrak: Faktor yang memicu minat investasi Fintech P2P Lending di Manado masih belum diketahui. P2P Lending berada pada puncak daftar Fintech Development di Indonesia pada 2018 dengan presentase 40%, yang mengindikasikan bahwa P2P Lending memiliki kesempatan besar bagi para investor untuk menemukan instrumen investasi alternatif. Penelitian ini bertujuan untuk menentukan faktor apa saja yang secara signifikan mempengaruhi minat investor P2P Lending di Manado untuk berinvestasi di platform P2P Lending. Secara spesifik, dalam cakupan Kemudahan yang dirasakan, Manfaat yang dirasakan, dan Jaminan Struktural. Dalam konteks ini, Minat Investasi didefinisikan sebagai perilaku pemberi dana, sebuah kehendak untuk meminjamkan uang pada platform P2P Lending yang juga dipertimbangkan sebagai sebuah langkah penting yang menentukan minat pemberi dana pada platform P2P Lending. Untuk menguji semua hipotesa bahwa Kemudahan yang dirasakan, Manfaat yang dirasakan, dan Jaminan Struktural mempunyai pengaruh positif yang signifikan pada Minat Investasi, kuesioner daring didistribusikan pada para investor P2P Lending di Manado, dan semua tanggapan dianalisa menggunakan analisa PLS-SEM dengan software SmartPLS. Hasil menunjukkan bahwa hanya Manfaat yang dirasakan yang memiliki pengaruh positif yang signifikan terhadap Minat Investasi. Hasil ini menyimpulkan bahwa nilai kebergunaan yang membawa dampak bagi pribadi investor adalah pemicu kuat bagi Minat Investasi investor P2P Lending di Manado.